A Study on Teachers' Deportments and Pedagogical Skills at the Intermediate Level in an EFL Context - Islam Khan, Mohammad Ehsanul; Maniam, Mahendran (AJELP: Asian Journal of English Language and Pedagogy, 2021)
The study depicted the classroom environment during the teaching and learning process, focusing on appraising the teachers' demeanour and pedagogical strategies in the intermediate classrooms of the 'English as foreign language (EFL)' context of Bangladesh. The intermediate level denotes the higher secondary level of the 11th and 12th grades. Sixteen teachers of eight intermediate institutions from three districts of Bangladesh were selected as the key participants of this study. The study used two tools: classroom observation and interview. The researchers observed the teachers' deportments both from the outside and inside the classroom. The teachers and the students were observed to understand the current classroom scenario by evaluating the teacher's interactions, abilities and inabilities to manage the EFL classrooms. The interview was conducted in the 'Key Informant Interviews (KII)' format to know their viewpoints about their classroom deportments. The study found that some teachers have yet to develop their classroom management techniques to teach intermediate learners effectively. Later, the teachers participated in KII to provide more information about their deportments in the classrooms that effectively reveal the limitations and development aspects of teaching in the higher secondary classrooms. The study finally recommended some imperative measures to be taken by the institutions’ management or the central authority.